2020
DOI: 10.3390/genes11091111
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Back Splicing, a Still Poorly Explored World: Non-Canonical Circular RNAs

Abstract: Most of the circRNAs reported to date originate from back splicing of a pre-mRNA, and these exonic circRNAs are termed canonical circRNAs. Our objective was to provide an overview of all other (non-canonical) circRNAs that do not originate from the junction of two exons and to characterize their common properties. Those generated through a failure of intron lariat debranching are the best known, even though studies on them are rare. These circRNAs retain the 2′–5′ bond derived from the intron lariat, and this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 53 publications
2
15
0
Order By: Relevance
“…CE2 was also able to detect the six intronic circRNAs from the DNAH17 previously reported ( Robic et al, 2019 ) but again with a lower number of CCRs than expected. These observations confirmed that CE2 is able to detect intronic circRNAs ( Das et al, 2020 ), but as suggested previously ( Robic and Kühn, 2020 ), the strong requests on the two paired-end reads as included in the CE2 algorithm could impair the characterization of intronic circRNAs. The dataset ssc_testis_1 had also been used to describe the first sub-exonic circRNAs ( Robic et al, 2020 ).…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…CE2 was also able to detect the six intronic circRNAs from the DNAH17 previously reported ( Robic et al, 2019 ) but again with a lower number of CCRs than expected. These observations confirmed that CE2 is able to detect intronic circRNAs ( Das et al, 2020 ), but as suggested previously ( Robic and Kühn, 2020 ), the strong requests on the two paired-end reads as included in the CE2 algorithm could impair the characterization of intronic circRNAs. The dataset ssc_testis_1 had also been used to describe the first sub-exonic circRNAs ( Robic et al, 2020 ).…”
Section: Resultssupporting
confidence: 88%
“…So far, intronic circRNAs have been identified only from coding genes (reviewed by Robic and Kühn, 2020 ), but the current study shows that lncRNAs can also be involved in the production of intronic circRNAs. In pigs, this study highlighted that the lncRNAs ENSSSCG00000048463 and ENSSSCG00000041596 generated intronic circRNAs, however at a low expression level, with 6 and 11 associated CCRs, respectively.…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations